Geology, regional diamond exploration and diamond provenance of the proterozoic diamondiferous Umkondo conglomerates, Umkondo group, eastern Zimbabwe - Zhou, Takawira (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2016)
The Umkondo Sedimentary Basin in eastern Zimbabwe has been studied by various individuals and organizations since 1901. Their interest had been in finding limestone and beryl and base metal deposits, especially copper, iron and uranium, but these occurrences had proved to be of no economic value (Watson, 1969). The recent discovery of placer diamonds within the Proterozoic basal conglomerates of the Umkondo Sedimentary Basin has now attracted worldwide interest in the basin's diamond economic potential, in understanding of the geology, and the diamond provenance of the Umkondo conglomerates. The Umkondo Sedimentary Basin basal conglomerate placer deposit might narrowly be defined as a mega-placer because of its sheer large size and high grades, especially on the 70,000 hectare western margin diamond dispersion halo where alluvial diamonds are being mined. Bluck, et al., (2005, pp 213) defines a diamond mega-placer as: . . . a number of linked deposits that are a result of one or a continuous process of transportation and deposition and holds or have held at least >= 50 million carats at >= 95% gem quality, for example, the Orange-Vaal dispersal, off the Kaapvaal craton in South Africa. On craton placers are residual, and transient placers are eroded and deposited into the exit drainage, while terminal placers, the final depositories of diamonds with the highest chances of being mega-placers are deposited into terminal basins like oceans and foreland basins. Though data is limited at the moment, the Umkondo conglomerates caratage is likely to run into hundreds of millions of carats, with a diamond gem content of between twenty and twenty-five percent, as is indicated from recent diamond production data. The greater part of the Umkondo diamonds are likely to be lodged beneath the deep gravels of the Middle and Lower Save River basin, because small remnant tilted mountain blocks and inselbergs forming the caps of hills are what remains of the host conglomerate on the western margin of the Umkondo Basin. Areas to be examined in this document will be the geology; the mode of formation of the Umkondo basin and its sedimentary system; the regional kimberlite exploration around the basin; and diamond production in the Marange diamond field, in order to come up with indications of the provenance of the diamonds within the Umkondo conglomerates. The kimberlite clusters in and around the Umkondo sedimentary basin have all proved to be barren or only nominally diamondiferous and that the kimberlites are between 200Ma and 500Ma and thus much younger than the greater than 1.1Ga Umkondo diamondiferous conglomerates. Studies so far undertaken have not managed to point to the origin, or provenance, of the Umkondo or Marange diamonds, which were discovered on the western edge of the Umkondo Basin and in the east of the basin below the Chimanimani Mountains along the Haroni River. This paper is an attempt to clear up some of the misconceptions surrounding the Marange diamond deposit and to raise interest in the urgent rquirement to study and understand the Umkondo Basin and the origin of its diamonds. The only meaningful studies on diamond occurrence and diamond exploration of the basin were undertaken from 1996 to 2006 by Kimberlitic Searches Zimbabwe (Pvt) Ltd, the then Zimbabwe kimberlite exploration arm of De Beers, Zimbabwe, in their quest to find kimberlites, which were thought to be related to the Umkondo alluvial diamond deposit. As will be shown in the following chapters, many of the discovered kimberlites range from very low grade to non-diamondiferous, and are much younger than the Umkondo conglomerates, whose diamonds are in turn a great deal older. Thus the basic question concerning the origin or provenance of the Umkondo placer diamonds still remains unresolved. Because of the sheer size of the basin, modern, wide-area-coverage, geophysical exploration methods become appropriate to effectively generate diamond potential targets for further examination. This document will attempt to collate various data available to paint a true picture of the state of exploration within the Umkondo Basin.
Keywords: Uncatalogued